2020
DOI: 10.1042/bsr20192712
|View full text |Cite
|
Sign up to set email alerts
|

Prefoldin subunits (PFDN1–6) serve as poor prognostic markers in gastric cancer

Abstract: Prefoldin subunits (PFDN), primarily known for co-chaperone function associated with cytoskeletal rearrangement, have been found involved in epithelial–mesenchymal transition (EMT) and cancer progression. However, studies focusing on the roles of PFDN in gastric cancer (GC) remain limited. The present study aims to evaluate the prognostic values of PFDN in GC. Prognostic roles of PFDNs were analyzed via the Kaplan–Meier platform, followed by subset analysis within various clinical parameters. High mRNA express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…Unfortunately, GC is difficult to diagnose at an early stage. Therefore, people are very interested in finding prognostic markers for these potentially curable patients [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, GC is difficult to diagnose at an early stage. Therefore, people are very interested in finding prognostic markers for these potentially curable patients [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The study found that the prefoldin subunit can be used as a strong indicator of poor prognosis of gastric cancer (GC), and the results of subgroup analysis in various clinical parameters show that different prefoldin subunits display different effects the overall survival situation (Table 1) [35].…”
Section: The Role Of Prefoldin Subunits In Human Tumors and Other Dismentioning
confidence: 99%
“…In other disease, there is no lack of research on PFDN1. Through the reference gene selection system for nasopharyngeal carcinoma gene expression Gastric cancer [35] Lung cancer [36] Colon cancer [37] Nasopharyngeal carcinoma [38] Mouse Lymphocyte development [27] Cytoskeletal defect [27] PFDN2 Oncogene Human γ-Synuclein [42] Gastric cancer [35] Breast cancer [40] Metastatic urothelial carcinoma [41] Plant [65] PFDN4 Oncogene Human Atherosclerosis [19] Gastric cancer [35,52] Breast cancer [48,49] Colon cancer [51] Hepatocellular carcinoma [50] Atopic dermatitis [53] PFDN6 Human Gastric cancer [35] Acute lymphocytic leukemia [64] Arabidopsis thaliana [76] DELLA [67] Caenorhabditis elegans FOXO [77] α PFDN3/VBP1 Anti-oncogene Human VHL [43] pVHL [44] hMSH4 [45] HDAC1 [46] Gastric cancer [35] Arabidopsis thaliana DELLA [67] Caenorhabditis elegans [66] PFDN5/MM1 Anti-oncogene Human c-Myc [99] TIF1β [101] Rabring7 [127] Egr-1 [128] ARFP/F [129] p73α [133] p63α [134] ΔNp63α [135] Gastric cancer [35] Secondary hyperparathyroidism [54,...…”
Section: The Role Of Prefoldin Subunits In Human Tumors and Other Dismentioning
confidence: 99%
“…The expression of PFDN2 in various subtypes of gastric cancer shows poor overall survival and is a biological indicator of poor prognosis. 26 In type 2 diabetes, anti-PFDN2 antibodies may be useful biomarkers for the disease. 27 PFDN2 has also undergone genetic changes in breast cancer.…”
Section: Pfdn2 Can Be Used As a Tumor Biomarkermentioning
confidence: 99%
“…This abnormal expression can also be used as a biomarker to indicate the prognosis of the disease, which is of great significance in assisting the decision-making of disease treatment. 2,3 In terms of structure, prefoldin has a special and flexible hydrophobic protein binding region, which can capture proteins. Therefore, it can be used as a nanobiological template and designed as a nanoactuator to capture nanocargoes with different charges and various sizes.…”
Section: Introductionmentioning
confidence: 99%